DENTIST’S ROLE IN COLLABORATIVE MANAGEMENT OF TETANUS PATIENT - Amaliah, Nurfitri; Indah Wardhany, Indriasti (Fakultas Kedokteran Gigi Unjani, 2024)
Tetanus was a life-threatening infection causing muscle contractions. The need for qualified collaborative management was crucial due to the potential for poor prognosis and complications. Dentists can contribute significantly to the treatment, as the mouth can be one of the entry points for tetanus-causing bacteria. A 45-year-old male tetanus inpatient was referred from the Intensive Care Unit to the Oral Medicine Unit at Universitas Indonesia Hospital to evaluate the possible source of oral focus infection. A boil was on his back, suspected to be the main port of entry for tetanus bacteria. The definitive diagnosis was Tetanus of moderate to severe severity (Philips score 24, Dakar score 1, Ablett score 2). Extra oral examination shows lip inflammation. An intra-oral examination cannot be done optimally despite his trismus. The oral foci of infection found were chronic gingivitis and pulp necrosis on 47 48, in addition to the diagnosis of cheilitis simplex. Since the comprehensive management of the foci of infection could only be done in an outpatient setting, the nurse was instructed to clean the intra-oral using sterile gauze moistened with NaCl 0.9% solution to improve the patient's oral hygiene (OH). Comprehensive management includes periodically visiting to maintain OH, administering muscle relaxants, antibiotics, and analgesics, and administering Tetanus toxoid vaccination. The patient was recovered. Management of tetanus cases needs a multidisciplinary approach. Dentists are pivotal in identifying oral infection sources and ensuring its management. A dentist's role in the collaborative management of tetanus patients might significantly contribute to the patient's prognosis. DOI : 10.54052/jhds.v3n3.p303-316